2010
DOI: 10.1007/s10230-010-0130-4
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Hardness of Mine Water Using Transformed Fly Ash

Abstract: In the Jharia Coalfields, Dhanbad, India, huge quantities of water are pumped out of underground mines to make mining possible. The water contains high concentrations of total hardness, which makes it unsuitable for domestic use. Waste fly ash generated nearby from burning the coal in thermal power plants can be converted into a zeolitic mineral, and used to treat the mine water. The fly ash zeolite was determined to be effective in removing total hardness from the mine water. At a 40 g/L dose of fly ash zeoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…The results clearly indicate that both ash types have potentials to use as water softening materials. However, the results contradicted with the findings from Prasad et al (2011) who reported that fly ash obtained from burning of coal increased total hardness of the mine water. The contrasting results might be related to different sources of ash, as the fly ash used in Prasad et al (2011) study contained much lesser concentration of K (1.0%) compared to the concentrations K in RHA (9.3%) and WSA (32.2%) used this study (Table 1).…”
Section: Resultscontrasting
confidence: 88%
See 2 more Smart Citations
“…The results clearly indicate that both ash types have potentials to use as water softening materials. However, the results contradicted with the findings from Prasad et al (2011) who reported that fly ash obtained from burning of coal increased total hardness of the mine water. The contrasting results might be related to different sources of ash, as the fly ash used in Prasad et al (2011) study contained much lesser concentration of K (1.0%) compared to the concentrations K in RHA (9.3%) and WSA (32.2%) used this study (Table 1).…”
Section: Resultscontrasting
confidence: 88%
“…The contrasting results might be related to different sources of ash, as the fly ash used in Prasad et al (2011) study contained much lesser concentration of K (1.0%) compared to the concentrations K in RHA (9.3%) and WSA (32.2%) used this study (Table 1). Prasad et al (2011), however, found that zeolite prepared from fly ash decreased hardness with increasing concentrations from 5 to 40 g/l. Prasad et al (2011) also reported that zeolite rapidly removed hardness for the first but slowed down after 30 min and reached to steady state within 4 hrs.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Several synthetic zeolites have been used for cation adsorption. For example, Prasad et al (2011) found that fly ash zeolite was able to remove 100 % Pb 2? , 99 % Cd 2?…”
Section: Zeolite-based Adsorbentsmentioning
confidence: 98%
“…Seeing the importance of groundwater quality in mining area, the investigation has been carried out to understand the changes in groundwater quality of Dhanbad township within 3 years of time duration (May 2011-May 2014. Heavy metal pollution index (HPI) of the groundwater has also been evaluated according to described methodology (Prasad and Jaiprakas 1999;Prasad and Bose 2001;Prasad and Kumari 2008;Prasad and Mandal 2008;Prasad et al 2011;Chabukdhara et al 2017). On the basis of this, groundwater quality of Dhanbad township has been predicted.…”
Section: Introductionmentioning
confidence: 99%